1973
DOI: 10.1111/j.1471-0528.1973.tb11230.x
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of Ovulation by Tamoxifen

Abstract: Summary A new anti‐oestrogen, tamoxifen, has been synthesized and is available for clinical trials. Its value in the treatment of anovulatory infertility has been assessed in 32 patients. A total of 26 patients apparently ovulated, 16 patients conceived during a treatment cycle, and 2 patients became pregnant during the first spontaneous cycle thereafter. There was no increase in the abortion rate and there were no multiple pregnancies. Side‐effects were uncommon and none were serious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 3 publications
2
45
1
1
Order By: Relevance
“…Our results were similar to those reported by Williamson and Ellis (1973) and Tajima et al (1977) and the time lag was between day 13 and 46 of the treatment, i.e. 22.5+ 1.4 on average, demonstrating a wider distribution.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results were similar to those reported by Williamson and Ellis (1973) and Tajima et al (1977) and the time lag was between day 13 and 46 of the treatment, i.e. 22.5+ 1.4 on average, demonstrating a wider distribution.…”
Section: Discussionsupporting
confidence: 81%
“…Treatment with 60 mg daily was considered necessary in order to induce satisfactory rates of ovulation in the patients of the first grade amenorrhea. According to Williamson and Ellis (1973) who investigated the relationship between the dosage level and the ovulation inducing rate, 20 mgdaily recorded a ovulatory response rate of 61.9%, 40 mg-daily did 60 and 80 mg-daily did 80%. When taking their results into account, tamoxifen might be administered at dosage level as high as 80 mg/daily, but at the same time, great cautions should be exercised on manifestation of adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Williamson et al reported an ovulation rate of 81% whereas another study by Messinis et al reported the ovulation rate as 76.08% while using tamoxifen for ovulation induction. 7,12 The pregnancy rates as seen in our study were found to be similar to those reported by Williamson et al and Fukushima et al,(35.5%) with the use of tamoxifen in cases of luteal phase defects. In patients of PCOS Gulekli et al reported an ovulation rate of 70% whereas Seyedoshohadaei F et al reported ovulation rate of 68% and pregnancy rate of 40%.…”
supporting
confidence: 80%
“…It is primarily used as an adjuvant therapy in the treatment of breast cancer but its use as an ovulatory agent was first reported in 1973. 7 Unlike clomiphene, tamoxifen acts as an agonist on the estrogen receptors of the vaginal mucosa and endometrium but studies on the effects of tamoxifen on cervical mucus have been inconclusive. Also there are no reports of increased chances of ovarian cancer with use of tamoxifen.…”
Section: Introductionmentioning
confidence: 99%
“…The drug was found to be an extremely potent postcoital contraceptive in the rat [4,5]. Unfortunately, ICI 46,474 did not exhibit antifertility properties in women, in fact, quite the opposite, it induced ovulation [6,7]. As a result, the medicine was, at one time, marketed in the United Kingdom for the induction of ovulation in subfertile women with a functional hypothalamo-pituitary-ovarian axis.…”
Section: Tamoxifen the First Sermmentioning
confidence: 99%